Crustal and Upper Mantle Shear Wave Velocity Structure of Botswana: The 3 April 2017 Central Botswana Earthquake Linked to the East African Rift System - Fadel, Islam; Paulssen, Hanneke; van der Meijde, Mark; Kwadiba, Motsamai; Ntibinyane, Onkgopotse; Nyblade, Andrew; Durrheim, Raymond (Geophysical research letters, 2020)
Rayleigh wave group and phase velocity measurements obtained from ambient noise and earthquake data at 51 broadband stations were used to construct the first 3‐D crustal and upper mantle shear wave velocity model of Botswana. The model shows low crustal velocities associated with the Passarge and Nosop sedimentary basins, whereas the Kaapvaal, Zimbabwe, Maltahohe, and Congo Cratons are recognized by high mantle velocities. The lowest upper mantle shear wave velocity, beneath northeastern Botswana, is associated with the southwestern branch of the East African Rift System. This low‐velocity mantle anomaly appears to be linked to the crust of the Okavango Rift Zone and the location of the 3 April 2017 Mw 6.5 earthquake in central Botswana. We suggest that fluids or melt at the base of the crust from the southward continuation of the East African Rift Zone triggered the intraplate earthquake in an extensional tectonic setting. Plain Language Summary We used seismic noise and data from large distant earthquakes recorded on seismic stations in Botswana and Namibia to produce 3‐D seismic velocity model of the crust and upper mantle of Botswana. Our model shows the deep sedimentary basins and the different cratons in the study area. Interestingly, our model shows the signature of the southwestern branch of the East African Rift System in the upper mantle at the northeastern tip of Botswana. The East African Rift System anomaly was found to be connected to the active Okavango Rift Zone and the location of the 3 April 2017 earthquake in central Botswana, the second largest earthquake in Botswana's history and the largest intraplate earthquake in the last 30 years. Our results suggest that fluids from the East African Rift System in the upper mantle have triggered the intraplate earthquake as part of the ongoing rifting in southern Africa. Key Points We provide the first 3‐D crustal and upper mantle shear wave velocity model of Botswana The model highlights different sedimentary basins and cratons The upper‐mantle low‐velocity anomaly of the East African Rift System connects to the central Botswana 2017 Mw 6.5 earthquake